2014
DOI: 10.1128/jb.02274-14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamics of a Bacillus subtilis Spore Germination Protein Complex during Spore Germination and Outgrowth

Abstract: Germination of Bacillus subtilis spores is normally initiated when nutrients from the environment interact with germinant receptors (GRs) in the spores' inner membrane (IM), in which most of the lipids are immobile. GRs and another germination protein, GerD, colocalize in the IM of dormant spores in a small focus termed the "germinosome," and this colocalization or focus formation is dependent upon GerD, which is also essential for rapid GR-dependent spore germination. To determine the fate of the germinosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Our results support the first model whereby CspB, CspA, and CspC are in a germinosome complex – similar to the germinosome complex found in B. subtilis [53]. Recent studies on GerS have shown that GerS likely does not form a complex with other germination proteins [52, 54].…”
Section: Discussionsupporting
confidence: 86%
“…Our results support the first model whereby CspB, CspA, and CspC are in a germinosome complex – similar to the germinosome complex found in B. subtilis [53]. Recent studies on GerS have shown that GerS likely does not form a complex with other germination proteins [52, 54].…”
Section: Discussionsupporting
confidence: 86%
“…2 ), an extension of this model is that CspC, CspB and CspA form a complex in dormant spores analogous to the B. subtilis germinosome signaling complex [72]. The CspB substrate SleC may also associate with this complex in mature spores, since CspC and CspB levels are reduced in a sleC mutant ([39], Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Individual knockout of all ger operons in B. cereus ATCC 14579 failed to identify a role in germination for three (GerK, GerL and GerS) out of the seven Ger receptors, although all operons were transcribed during sporulation 16 . Clarification of the structure-function relationship of Ger receptors has also been hindered by the difficulty to isolate functional receptors, because they are membrane complexes composed of three subunits and associated with other proteins in a so-called germinosome complex 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%